Analysis of the Use of Science Instructional Media in the High Grade of State Elementary School 52 in Lima Puluh Sub-District, Pekanbaru City - Crysty, Regina; Adiputra, M. Jaya; Syahrilfuddin, Syahrilfuddin (Proceedings of the UR International Conference on Educational Sciences, 2018)
The use of science learning media has become an obligation of learning as the implementation of active learning curriculum. This study analyzes the teachers comprehension of the use of instructional media in schools, especially the science intructional media in the high grade of elementary schools. The observed components include teacher comprehension of media, creativity, skills, objectivity, facilities and infrastructure, learning format, practicality, motivation, endurance, suitability of learning objectives, goals of science as an output, science objectives as a process, science objectives as a scientific attitude, conformity media, student learning styles and flexibility. The results of this study indicate that teachers have used intructional media, but tend to procedural according to the guidebook and learning media tend to be only as a complement to learning, does not lead to the learning objectives of science.